2018
DOI: 10.1037/spy0000125
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional perfectionism in sport: A meta-analytical review.

Abstract: Research at York St John (RaY) is an institutional repository. It supports the principles of open access by making the research outputs of the University available in digital form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
118
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(138 citation statements)
references
References 69 publications
(115 reference statements)
14
118
2
4
Order By: Relevance
“…These findings align with those of several studies that have reported more adaptive relations between features of PS (and more maladaptive relations between features of PC) and autonomous forms of motivation. 15,51 While residual PSP has a favourable effect on athletes' self-determined motives, residual CMP is accompanied by less desirable, non-self-determined motives. There was also evidence of an indirect effect linking residual PSP with SDM via MT, providing preliminary support for the partial mediating mechanism of MT.…”
Section: Discussionmentioning
confidence: 99%
“…These findings align with those of several studies that have reported more adaptive relations between features of PS (and more maladaptive relations between features of PC) and autonomous forms of motivation. 15,51 While residual PSP has a favourable effect on athletes' self-determined motives, residual CMP is accompanied by less desirable, non-self-determined motives. There was also evidence of an indirect effect linking residual PSP with SDM via MT, providing preliminary support for the partial mediating mechanism of MT.…”
Section: Discussionmentioning
confidence: 99%
“…This is relevant to the context of the re-sults presented insofar that the higher the level of positive perfectionism in a person, the higher is his/her desire to give their best performance and the higher is the possibility of elite performance in sports (Gould, Dieffenbach, & Moffett, 2002). Some athletes, however, show detrimental perfectionistic tendencies in exercise performance and in disordered eating (Hill, Mallinson-Howard, & Jowett, 2018). One study found that a striving for perfectionism combined with narcissism predicted a greater degree of exercise dependence (Miller & Mesagno, 2014).…”
Section: Correlations Between Food Addiction Exercise Dependence Anmentioning
confidence: 99%
“…Há também um grande risco de comportamentos obsessivos e transtornos alimentares entre artistas, por conta de uma estrutura corporal muito específica que deve ser alcançada e mantida em determinadas ocupações (Hays, 2002). É importante enfatizar que, ao contrário do que pode se pensar no senso comum, o perfeccionismo e a obsessão não são necessariamente adaptativos em contextos de alta performance, uma vez que a inflexibilidade e comportamentos autodestrutivos estão associados a esses traços (Hill, Mallinson--Howard, & Jowett, 2018;Hill, Witcher, Gotwals, & Leyland, 2015).…”
Section: Mundo Artísticounclassified